Submarine Shallow-Water Fluid Emissions and Their Geomicrobiological Imprint: A Global Overview - Caramanna, Giorgio; Sievert, Stefan M.; Bühring, Solveig I. (Frontiers in Marine Science, 2021)
Submarine fluids emissions in the form of geothermal vents are widespread in a variety of geological settings ranging from volcanic to tectonically active areas. This overview aims to describe representative examples of submarine vents in shallow-water areas around the globe. The areas described include: Iceland, Azores, Mediterranean Sea (Italy and Greece), Caribbean, Baja California, Japan, Papua, New Zealand, Taiwan. Common and divergent characteristics in terms of origin and geochemistry of the emitted fluids and their impact on the indigenous organisms and the surrounding environment have been identified. In the hottest vents seawater concentration is common as well as some water vapor phase separation. Carbon dioxide is the most common gas often associated with compounds of sulfur and methane. In several vents precipitation of minerals can be identified in the surrounding sediments. The analyses of the microbial communities often revealed putative chemoautotrophs, with Campylobacteria abundantly present at many vents where reduced sulfur compounds are available. The techniques that can be used for the detection and quantification of underwater vents are also described, including geophysical and geochemical tools. Finally, the main geobiological effects due to the presence of the hydrothermal activity and the induced changes in water chemistry are assessed.